Corporate Social Responsibility Programs In the Principles of Sharia Economic Law - Fauziah, Fauziah; Harun, Muhamad; Sari, Resty Okta Iman (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Limited Liability Companies a role in economic development and must be responsible for the surrounding environment in its business activities, known as CSR. Thus, it is necessary to know the arrangements regarding the CSR program. Reviewing the CSR program from the point of view of sharia economic law is also necessary. Therefore, researchers conducted research related to the CSR program to examine the program based on the principles of Islamic economic law. This research is qualitative research using secondary data. Data was collected through a documentation study. Data analysis technique was carried out in qualitative descriptive. This study found that arrangements regarding CSR programs must pay attention to ethical, moral, and mandatory principles for Limited Liability Companies. This principle is compatible with the principles of sharia economic law, such as the principle of permissibility, the principle of freedom of contract, the principle of agreement, the principle of binding promises, the principle of balance, the principle of benefit, and the principle of justice. CSR in the perspective of Sharia Economic Law, is a consequence of Islamic teachings. It means that a company must not be concerned with itself but must also pay attention to the surrounding environment.